Strengthening Posyandu Institutions in Handling Stunting Problems - Irfan Hilmi, Muhammad; Rahmawati, Ira; Tri Indrianti, Deditiani (Universitas Pendidikan Indonesia (UPI), 2020)
One effort in dealing with stunting in the community is bystrengthening the POSYANDU institution. In the process ofcommunity empowerment, institutional strengthening is needed aspart of the organization of women's abilities that have been obtainedand then strengthened in institutions that will eventually occur tolearn from one another and as an institutionalized learning exchangeprocess. Through institutional strengthening it is hoped that theacquisition of information, knowledge and skills will continue to beinstitutionalized in social organizations, especially those relating tostunting prevention and handling in Jelbuk Village. The serviceslearned are based on a qualitative approach with descriptivemethods. The subjects of this community service activity were PKKand POSYANDU cadres from Jelbuk village. Data collectiontechniques are done using interviews, observation and studydocumentation. The findings show that the POSYADU institutionalstrengthening strategy can be carried out through strengtheningUKBM management and Health Program Advocacy.